A new Basal sauropodomorph dinosaur from the Lower Jurassic Navajo sandstone of Southern Utah. - Joseph J W Sertich (Public Library of Science (PLoS), 2010)
Background Basal sauropodomorphs, or 'prosauropods,' are a globally widespread paraphyletic assemblage of terrestrial herbivorous dinosaurs from the Late Triassic and Early Jurassic. In contrast to several other landmasses, the North American record of sauropodomorphs during this time interval remains sparse, limited to Early Jurassic occurrences of a single well-known taxon from eastern North America and several fragmentary specimens from western North America. Methodology/principal findings On the basis of a partial skeleton, we describe here a new basal sauropodomorph dinosaur from the Lower Jurassic Navajo Sandstone of southern Utah, Seitaad ruessi gen. et sp. nov. The partially articulated skeleton of Seitaad was likely buried post-mortem in the base of a collapsed dune foreset. The new taxon is characterized by a plate-like medial process of the scapula, a prominent proximal expansion of the deltopectoral crest of the humerus, a strongly inclined distal articular surface of the radius, and a proximally and laterally hypertrophied proximal metacarpal I. Conclusions/significance Phylogenetic analysis recovers Seitaad as a derived basal sauropodomorph closely related to plateosaurid or massospondylid 'prosauropods' and its presence in western North America is not unexpected for a member of this highly cosmopolitan clade. This occurrence represents one of the most complete vertebrate body fossil specimens yet recovered from the Navajo Sandstone and one of the few basal sauropodomorph taxa currently known from North America.